Tracking the South African marketing index - Alwyn P. Du Plessis; Christo Boshoff (South African Journal of Business Management, 1997)
This study analyses marketing and marketing activities from a consumer's point-of-view. It measures consumer attitudes towards the so-called 4 Ps (product, price, promotion and retailing) and converts these scores to an overall 'attitude towards marketing' index. It also compares the results of similar studies conducted in previous years. A survey of randomly selected South African consumers reveals that the South African Marketing Index is +22.28 (in the range -200 to +200) suggesting reasonably favourable perceptions of marketing and marketing practices. This is the first time since the commencement of this longitudinal study that the overall marketing index has been positive. The most favourable individual index is the retailing index (+22.91), followed by the price index (+13.11). Both the product and the advertising indices are, however, negative (-5.49 and -1.33 respectively).
Keywords: 650